Social responsibility by Australian football clubs in the 1890s. Issue 3 (11th October 2019) - Halabi, Abdel
Abstract : Purpose: This paper aims to examine the social responsibility (SR) by Australian football clubs during the late nineteenth century. While there has been some contemporary research linking SR with sporting clubs, there is a dearth of such studies in the historical context. Design/methodology/approach: This paper uses a qualitative approach and in the absence of annual reports, relies on The Suburban newspaper narratives of club annual general meetings (AGMs). The National Library of Australia's newspaper digitisation programme was used which is a unique archive in management research. Findings: Even though it was well-known that football provided a social outlet for watching games, this paper found clubs also engaged in a number of SR-related activities that benefited many stakeholders and the surrounding communities. Originality/value: Deficient in much of the history of Australian football is the SR that clubs displayed to their stakeholders. This paper lengthens the historical SR literature for sporting clubs, and provides rich and detailed evidence of SR. While Australian football club histories continue to highlight winning teams, premierships and major personalities, their SR contribution is also significant and extends to the foundation of the game.